Dermorphin [D-Arg2, Lys4] (1-4) amide inhibits below-level heat hypersensitivity in mice after contusive thoracic spinal cord injury. Issue 12 (December 2019) - Liu, Shuguang; Huang, Qian; He, Shaoqiu; Chen, Zhiyong; Gao, Xinyan; Ma, Danxu; Duan, Wanru; Ford, Neil; Yang, Fei; Chen, Xueming; Raja, Srinivasa N.; Hao, Dingjun; et al.
Abstract : Abstract: Opioid use for chronic pain is limited by severe central adverse effects. We examined whether activating mu-opioid receptors (MORs) in the peripheral nervous system attenuates spinal cord injury (SCI) pain-like behavior in mice. We produced a contusive SCI at the T10 vertebral level and examined motor and sensory dysfunction for 6 weeks. At 6 weeks, we tested the effect of subcutaneous (s.c.) injection of dermorphin [D-Arg2, Lys4] (1-4) amide (DALDA), a peripherally acting MOR-preferring agonist, on mechanical and heat hypersensitivity. Basso mouse scale score was significantly decreased after SCI, and mice showed hypersensitivity to mechanical and heat stimulation at the hind paw beginning at 2 weeks, as indicated by increased paw withdrawal frequency to mechanical stimulation and decreased paw withdrawal latency to heat stimulation. In wild-type SCI mice, DALDA (1 mg/kg, s.c.) attenuated heat but not mechanical hypersensitivity. The effect was blocked by pretreatment with an intraperitoneal injection of methylnaltrexone (5 mg/kg), a peripherally restricted opioid receptor antagonist, and was also diminished in Pirt -MOR conditional knockout mice. DALDA did not adversely affect exploratory activity or induced preference to drug treatment in SCI mice. In vivo calcium imaging showed that DALDA (1, 10 mg/kg, s.c.) inhibited responses of small dorsal root ganglion neurons to noxious heat stimulation in Pirt -GCaMP6s mice after SCI. Western blot analysis showed upregulation of MOR in the lumbar spinal cord and sciatic nerves at 6 weeks after SCI. Our findings suggest that peripherally acting MOR agonist may inhibit heat hypersensitivity below the injury level with minimal adverse effects. Abstract : Supplemental Digital Content is Available in the Text.This study shows upregulations of mu-opioid receptor expression in the lumbar spinal cord and sciatic nerves after thoracic spinal cord injury and inhibition of heat hypersensitivity by DALDA in mice.